2016
DOI: 10.1104/pp.15.01335
|View full text |Cite
|
Sign up to set email alerts
|

CURLY LEAF Regulates Gene Sets Coordinating Seed Size and Lipid Biosynthesis

Abstract: ORCID IDs: 0000-0003-1338-523X (J.L.); 0000-0001-6872-9373 (S.D.).CURLY LEAF (CLF), a histone methyltransferase of Polycomb Repressive Complex 2 (PRC2) for trimethylation of histone H3 Lys 27 (H3K27me3), has been thought as a negative regulator controlling mainly postgermination growth in Arabidopsis (Arabidopsis thaliana). Approximately 14% to 29% of genic regions are decorated by H3K27me3 in the Arabidopsis genome; however, transcriptional repression activities of PRC2 on a majority of these regions remain u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 76 publications
6
53
0
Order By: Relevance
“…This energetic trade-off has been observed in genetic mutants such as APETALA2 495051 and CURLY LEAF28 52. In this study we showed that manipulation of the auxin pathway in J.curcas not only increased seed size but also enhanced total seed yield.…”
Section: Discussionsupporting
confidence: 73%
“…This energetic trade-off has been observed in genetic mutants such as APETALA2 495051 and CURLY LEAF28 52. In this study we showed that manipulation of the auxin pathway in J.curcas not only increased seed size but also enhanced total seed yield.…”
Section: Discussionsupporting
confidence: 73%
“…6). This is resonant with the recent report in mouse that re-establishment of H3K4me3 occurs more rapidly than that of H3K27me3 during activation of the zygote genome [Liu, 2016. In mammalian cells, deposition of H3K27me3 by PcG proteins is hindered by the presence of H3K4me3 [Schmitges, 2011.…”
Section: Integrative Analysis Of Chromatin and Transcription Datasetssupporting
confidence: 60%
“…A similar result of higher intronic transcript levels was found in clf‐28 shoot (Fig. S1c) (Liu et al ., ).…”
Section: Resultsmentioning
confidence: 97%